PENGARUH PENDEKATAN PEMBELAJARAN DAN KEMAMPUAN AWAL TERHADAP HASIL BELAJAR PADA MATA PELAJARAN SAINS DI SEKOLAH DASAR NEGERI 1 PAGUYAMAN KECAMATAN PAGUYAMAN PANTAI KABUPATEN BOALEMO - Hamzah B Uno; Nina Lamatenggo (Akademika : Jurnal Teknologi Pendidikan, 2018)
The purpose of this study was to (1) knowing the difference of students studying in science subjects are studied by using individual learning approach that uses the group learning approach. (2) know the interactions between learning approach and the initial capacity of students learning outcomes in subjects science. (3) know the difference results of learners studying in science subjects that have high initial capacity and learning through individual learning approach and the group learning approach (4) know the difference results of learners studying in science subjects with low initial ability and learning through individuallearning approach and the group learning approach. This study uses the method on two classes eksprimen who had treated the class got a treat with eksprimen materials science teach individual approach and the control class received treatment through group learning approach. The data in this study using the test results of 28 studies on learners. The data analyzed in this study is descriptive and inferential. The research concluded that (1) On the whole the results of studying science subjects that students learn with individual learning approach does not provide significant differences in learning results in science subjects students are studying with a group learning approach. This means that the overall approach to learning kemangkusan individual is better than the group learning approach. (2) There is interaction between learning and the ability modeol beginning to learn to appreciate the science lesson. This means that individual learning approach is superior to the group learning approach for students who have a high initial capacity, while for students who have low initial ability is more suited to group learning approach. (3) Learners who have a high initial capacity, individual learning approach to learning results in science subjects better when compared with the results of studying science subjects in the group learning approach. (4) For pupils who have a high initial capacity, individual learning approach to learning results in science subjects better when compared with the results of studying science subjects in the group learning approach.